2006
DOI: 10.1245/s10434-006-9247-x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Adjuvant Radioimmunotherapy after Cytoreductive Surgery in Experimental Peritoneal Carcinomatosis of Colorectal Origin

Abstract: The efficacy of adjuvant RIT after CS for the treatment of PC of colonic origin decreases when the administration of the radiolabelled MAbs is postponed. This study shows that adjuvant RIT should be given as early as possible after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…The predicted dose would be 104 Gy in a 1-mm metastasis, 24.5 Gy in a 100-mm micrometastasis, and 3.9 Gy in a 10-mm single tumor cell. Although small tumors are more radiosensitive than macrometastases (10,11), the low dose delivered by 177 Lu to isolated cells might not be sufficient to destroy them all. However, the dose delivered by a hypothetical 161 Tb-labeled somatostatin analog (with the same tumor affinity) would be 1.8 times higher in a 100-mm micrometastasis (44.5 Gy) and 3.6 times higher in a 10-mm single cell (14.1 Gy) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predicted dose would be 104 Gy in a 1-mm metastasis, 24.5 Gy in a 100-mm micrometastasis, and 3.9 Gy in a 10-mm single tumor cell. Although small tumors are more radiosensitive than macrometastases (10,11), the low dose delivered by 177 Lu to isolated cells might not be sufficient to destroy them all. However, the dose delivered by a hypothetical 161 Tb-labeled somatostatin analog (with the same tumor affinity) would be 1.8 times higher in a 100-mm micrometastasis (44.5 Gy) and 3.6 times higher in a 10-mm single cell (14.1 Gy) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hypoxia increases resistance to radiation. Experimental data in rodents also showed better efficacy on microscopic metastases (10,11).…”
mentioning
confidence: 87%
“…10 The effect was most explicit when RIT treatment was administered immediately following surgery, as compared to 4 or 14 days after surgery. 11 In rats with intraperitoneal CC531 tumors, RIT was found to be at least as effective as HIPEC in terms of survival after CS, and RIT induced fewer side effects than the adjuvant treatment with HIPEC. 12 These experiments suggest that RIT is a promising therapeutic approach to ameliorate treatment of PC.…”
Section: Introductionmentioning
confidence: 93%
“…In a model with resected peritoneal carcinomatosis, the 177 Lu-MG1 antibody improved survival after cytoreductive surgery as compared to chemotherapy. 44, 45 Koppe et al also demonstrated the efficacy of RIT in peritoneal carcinomatosis after cytoreductive surgery. 49 In these studies, rats were first injected intraperitoneally with 2 · 10 6 CC-531 cells and tumors were allowed to grow for 14 days.…”
Section: Impact Of A-particles On the Peritoneummentioning
confidence: 98%
“…However, several recent studies have modeled minimal residual and metastatic disease in rat and mouse models and evaluated the efficacy of RIT. [38][39][40][41][42][43][44][45] Some of the models of minimal disease and the RIT strategies employed in these studies are schematically described in Figure 1.…”
Section: Impact Of A-particles On the Peritoneummentioning
confidence: 99%